Regulating human research : IRBs from peer review to compliance bureaucracy - Babb, Sarah L. (Stanford University Press, 2020)
This book traces the historic transformation of institutional review boards (IRBs) from academic committees to compliance bureaucracies. Sarah Babb opens the black box of contemporary IRB decision-making, which is increasingly outsourced to specialized private firms.